2017
DOI: 10.1007/s10029-017-1610-2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products as a biomarker for incisional hernia

Abstract: BackgroundIncisional hernia is one of the most frequent complications after abdominal surgery, with incidences up to 30%. A reliable biomarker for the prediction of this complication is lacking. Advanced glycosylation end products (AGEs), also known as non-enzymatic collagen crosslinks, are correlated with aging, smoking, hyperglycemia, hyperlipidemia and oxidative stress. In this study the accumulation of AGEs and the relation between AGEs and incisional hernia were investigated.Materials and methodsIn an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
3
0
2
Order By: Relevance
“…A recent Dutch study found that advanced glycation end products (AGEs) might be used as a biomarker for incisional hernia. Measurements based on the use of a Skin Auto Fluorescence (SAF) reader revealed that AGEs were significantly higher in patients with incisional hernia than in the control group (88). AGEs are harmful compounds generated by non-specific glycation of proteins and lipids which are related to cardiovascular diseases, arteriosclerosis, and neurodegeneration (89).…”
Section: Discussionmentioning
confidence: 99%
“…A recent Dutch study found that advanced glycation end products (AGEs) might be used as a biomarker for incisional hernia. Measurements based on the use of a Skin Auto Fluorescence (SAF) reader revealed that AGEs were significantly higher in patients with incisional hernia than in the control group (88). AGEs are harmful compounds generated by non-specific glycation of proteins and lipids which are related to cardiovascular diseases, arteriosclerosis, and neurodegeneration (89).…”
Section: Discussionmentioning
confidence: 99%
“…For each patient with SP, we assigned one who was never diagnosed with SP via propensity score matching. The matching variables were age; sex; index year; and comorbidities including hypertension (ICD-9-CM codes 401-405) [13,14], diabetes (ICD-9-CM codes 250) [15,16], hyperlipidemia (ICD-9-CM code 272) [17] and smoking related disease (ICD-9-CM codes 305.1, 430-438, 410-414, 493 and 496) [18].…”
Section: Study Populationmentioning
confidence: 99%
“…Other experiments include development of stronger suture material (polyurethane), and mesh derived sutures (for better resistance against suture cut-through) for abdominal closure [67,68]. Recently biomarkers (proteins assays associated with wound healing, advanced glycation end products/ collagen cross links) have been shown to predict personal hernia risk prior to undergoing an operation; if validated, tests for these can be included in hernia prediction models [69,70].…”
Section: Safety Of Synthetic Mesh In Presence Of Infection and Strangulationmentioning
confidence: 99%